{3,3′,5,5′-Tetramethoxy-2,2′-[ethane-1,2-diylbis(nitrilomethylidyne)]diphenolato}copper(II) - Assey, Gervas (International Union of Crystallography, 2010)
In the title square-planar copper complex, [Cu(C(20)H(22)N(2)O(6))], the Cu—N and Cu—O bond lengths are significantly longer than those of its isostructural nickel analog. The title structure is related to that of the corresponding monohydrate. There are significant differences in the conformations of the two complexes. While the monohydrate is mainly planar, in the title compound there is a slight twist in the two benzene rings at each end of the complex [dihedral angle = 13.14 (6)°]. All the atoms of the methoxy substitutents are in the plane of the ring to which they are attached (r.m.s. deviation = 0.0079 Å) except for one of the methoxy C atoms, which deviates slightly [0.309 (4) Å]. In the crystal, weak C—H⋯O intermolecular interactions link the molecules.